TEACHING OF LIFE FOUND IN MICHAEL JACKSON’S SONGS - Durrotul Aimmah; Budi Susatyo; Dholiful Hadi (Universitas PGRI Ronggolawe Tuban, 2024)
The purpose of the study is to find out the answer of statement of the problem: What is teaching of life found in Michael Jackson’s songs and how it described in Michael Jackson’s songs. This study uses descriptive qualitative research design in which it starts collecting and review research literature to provide the data and examine data for intention of the study. This research uses objective approach in analyzing the study, because the writer does not need to study at author’s life, background of the work, or background of the society but just analyzed the whole itself. The object of the study is Michael Jackson text songs which focused on the Teaching of life that found in Michael Jackson’s songs. The result of this research is that the writer finds some teaching of life related with moral, peace and love in Michael Jackson’s Songs. First, the writer finds teaching of life about moral covering struggle and equality in Michael Jackson’s songs entitled “Beat It”, “Black or White”. Second, the writer finds teaching of life about peace covering careness, brotherhood, and world peace in Michael Jackson’s songs entitled “Heal The World”, “Earth Song” and “Black Or White”. The last, the writer finds teaching of life about love covering love between human being and the importance of love for human life in Michael Jackson’s song entitled “I’ll Be There” and “Heal The World”.